2015
DOI: 10.1093/rpd/ncv462
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of the Swiss Population by Radiodiagnostics: 2013 Review

Abstract: In 2013, a nationwide investigation was conducted in Switzerland to establish the population's exposure from medical X rays. A hybrid approach was used combining the Raddose database accessible on-line by the participating practices and the Swiss medical tariffication system for hospitals. This study revealed that the average annual number of examinations is 1.2 per inhabitant, and the associated annual effective dose is 1.4 mSv. It also showed that computed tomography is the most irradiating modality and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…The two levels of dose were used to generate two independent image datasets. The 15 mGy acquisition corresponds to local dose reference level for abdominal imaging and is therefore representative of clinical practice. The scans were acquired and reconstructed with an abdominal protocol used routinely for clinical imaging on a multidetector CT (Discovery HD 750, GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…The two levels of dose were used to generate two independent image datasets. The 15 mGy acquisition corresponds to local dose reference level for abdominal imaging and is therefore representative of clinical practice. The scans were acquired and reconstructed with an abdominal protocol used routinely for clinical imaging on a multidetector CT (Discovery HD 750, GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…Modern CT equipment and technique development have provided tools for potential dose reduction, but the collective population dose is still increasing due to the increase in the number of CT examinations performed. Studies focusing on the potential for dose reduction due to technical improvements are therefore urgently needed [1][2][3][4]. Standardization and optimization of clinical protocols is therefore advocated to keep the radiation dose as low as reasonably achievable (ALARA) [5] while the diagnostic confidence is maintained.…”
Section: Introductionmentioning
confidence: 99%
“…A survey performed in 2006 in the United States showed that the average effective dose due to CT reached 1.5 mSv per capita, per year . The last surveys performed in Switzerland in 2008 and 2013 showed a similar trend, with the average dose per capita from CT increasing from 0.8 mSv to 1.0 mSv within this 5‐year period …”
Section: Introductionmentioning
confidence: 99%
“…2 The last surveys performed in Switzerland in 2008 and 2013 showed a similar trend, with the average dose per capita from CT increasing from 0.8 mSv to 1.0 mSv within this 5-year period. 3,4 e153…”
Section: Introductionmentioning
confidence: 99%